The History and Development of the Percutaneous Pedicle Screw (PPS) System - Ken Ishii; Haruki Funao; Norihiro Isogai; Takanori Saito; Takeshi Arizono; Masahiro Hoshino; Koji Sato (Medicina, 2022)
Minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) using the SEXTANT® system (Medtronic) featured the first generation of commercially available percutaneous pedicle screw (PPS) system in 2001. The innovative system has since become standard instrumentation used worldwide, and PPS is now used for long-segment minimally invasive surgery (MIS) spinal fixation from the thoracic spine to the pelvis for pathological conditions. PPS systems have been developed for approximately 20 years for the purpose of improving minimally invasive techniques, safety of instrumentation, and ease of use. The third-generation PPS systems established the insertion technique, and the development of the fourth-generation PPS systems have made great strides in minimizing the number of steps in the operative procedure. In the future, PPS systems are expected to continue making use of the latest technological advancements and to develop further with the aim of ensuring greater safety, reducing operator stress, and preventing complications such as insertion errors and infection. In this review article, we describe the historical evolution from the first-generation PPS system to the current PPS systems used today.